PENGARUH GREEN PRODUCT DAN BRAND TRUST TERHADAP MINAT BELI AIR CONDITIONER (AC) MEREK SHARP PADA BATAM CENTRAL ELEKTRONIK PEKANBARU - Christyanto, Danu; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted by conducting a consumer survey in Batam Central Elektronik Pekanbaru which is located at Taman Anglek Complex, Tuanku Tambusai Street, Number A4-A5. The purpose of this study is to determine the effect of green product and brand trust on the purchase intention Air Conditioner (AC) Brand Sharp. In this research using quantitative data analysis method with SPSS program. The sample in this study amounted to 92 respondents. Methods of data collection by distributing questionnaires. The results of this study is the response of respondents to the green product and brand trust in the category agree, while purchase intention in the category hesitant. While t test that has been done shows that the green product and brand trust partially have a significant effect on purchase intention. And F test results show that green product and brand trust simultaneously have a significant effect on purchase intention. The result of coefficient of determination test shows that green product and brand trust partially influence to the purchase intention of each of 60,4% and 67,3%, whereas simultaneously equal to 70,5% the rest influenced other variable not examined in this research.Keywords: Green Product, Brand Trust, Purchase Intention